Fibre Optic Sensors for the Structural Health Monitoring of Building Structures. (2016) - Bremer, K.; Wollweber, M.; Weigand, F.; Rahlves, M.; Kuhne, M.; Helbig, R.; Roth, B.
Abstract: In this work different fibre optic sensors for the structural health monitoring of civil engineering structures are reported. A fibre optic crack sensor and two different fibre optic moisture sensors have been designed to detect the moisture ingress in concrete based building structures. Moreover, the degeneration of the mechanical properties of optical glass fibre sensors and hence their long-term stability and reliability due to the mechanical and chemical impact of the concrete environment is discussed as well as the advantage of applying a fibre optic sensor system for the structural health monitoring of sewerage tunnels is demonstrated.